Extrapulmonary Tuberculosis Cases in an Infectious Diseases Department - Keskinel, İlkay; Güntürk, Arzu (Cerrahpaşa Medical Journal, 2025)
Objective: Tuberculosis (TB) remains a significant public health problem in Türkiye. We aimed to document cases diagnosed as TB while being investigated for fever of unknown origin, meningitis, pleurisy, lymphadenopathy, and other clinical pictures in an infectious diseases department. Methods: We reviewed the records of the Infectious Diseases Department of a Medical Faculty retrospectively and evaluated all patients with Mycobacterium tuberculosis infection hospitalized between January 1989 and October 1998. Results: One hundred eighty-four cases diagnosed as TB were enrolled. Forty-seven percent of the patients were male. Mean age was 30 years (range: 14-76). Extrapulmonary TB was diagnosed in 157 (85%) of the patients. The distribution of the cases was as follows: miliary (27%), lymphadenitis (21%), meningitis (12%), pleural (12%), peritoneal (14%), bone (7%), and other (10%). Pulmonary TB frequency was 15%. Tuberculin skin tests were positive in 85 of 164 patients. The methods of diagnosis were acid-fast smear (60/184), culture (17/184), histology (101/184), and clinical/radiological/therapeutic test (72/184). Conclusion: Extrapulmonary TB is still a persistent problem in Türkiye. This study highlights the unique spectrum of extrapulmonary TB observed in a tertiary care center, with miliary TB being more prevalent than in national and international reports, emphasizing the need to consider departmental focus and patient demographics. Cite this article as: Keskinel İ, Güntürk A. Extrapulmonary tuberculosis cases in an infectious diseases department. Cerrahpaşa Med J 2025; 49, 0023, doi: 10.5152/cjm.2025.24023.